The role of primary co-operatives in economic growth at Elim in Limpopo Province, South Africa - Tlakula, Motlatso Brian (My University, 2016)
The Co-operatives and Small Medium Micro Enterprises (SMME) sector in general is known to be synonymous with job creation and economic growth. The cooperative movement is said to have a potential of aiding unemployment and poverty in South Africa. The present study aimed at identifying the role of primary-cooperatives in economic growth at Elim in Limpopo Province. The study sought to find out what were the potential growth factors and opportunities available for co-operatives. It is also to examine the effectiveness of primary cooperatives as drivers of economic growth. The study was carried out at Elim in Limpopo Province. The methods used were questionnaires and interviews with primary co-operative members. A purposive sampling method was used because the researcher intended to interview specific members of the cooperative. Data were collected using both self-administered questionnaire and interviews. The findings of the study revealed that the majority of these co-operatives are not growing, thus becoming unsustainable. They are also unable to drive the local economy and impact positively to such economies. Lack of access to markets and other resources has been identified in the study as a serious challenge opposed to the success to these enterprises. Subsequent to that are issues pertaining to shortage and lack of, in certain instances, business skills and education amongst members. Finally, the study provides recommendations on the impact of cooperatives on the growth of the economy and how these can be revitalized to benefit not only the local economy at the community level, but also the entire nation.
Thesis (MBA.) --University of Limpopo, 2016
Keywords: Primary cooperative; Cooperatives; Economy; Challenges; Government; Markets; Small business; Economy; Economic development -- South Africa, Limpopo